2012
DOI: 10.1074/jbc.m111.297036
|View full text |Cite
|
Sign up to set email alerts
|

Alix Protein Is Substrate of Ozz-E3 Ligase and Modulates Actin Remodeling in Skeletal Muscle

Abstract: Background: Alix participates in fundamental cellular processes, but how it is regulated remains unknown. Results: Alix is ubiquitinated by the Ozz-E3 ligase and participates in actin cytoskeleton remodeling, filopodia formation, and myoblast migration. Conclusion: Ozz influences Alix conformation and in turn the extent of ubiquitination in Alix. Significance: Ozz-E3 ligase regulates Alix concentration at sites where the actin cytoskeleton undergoes remodeling.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
0

Year Published

2013
2013
2018
2018

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(55 citation statements)
references
References 44 publications
6
49
0
Order By: Relevance
“…We have shown previously that, in muscle cells, Alix is one of the substrates of the RING‐type ubiquitin ligase, Ozz‐E3 [8]. This ligase complex includes the substrate‐recognition module Ozz, as well as Elongin B and C, Rbx1 and Cullin 5 [11].…”
Section: Resultsmentioning
confidence: 99%
“…We have shown previously that, in muscle cells, Alix is one of the substrates of the RING‐type ubiquitin ligase, Ozz‐E3 [8]. This ligase complex includes the substrate‐recognition module Ozz, as well as Elongin B and C, Rbx1 and Cullin 5 [11].…”
Section: Resultsmentioning
confidence: 99%
“…The establishment of actin cytoskeletal interactions with the extracellular matrix and between cells is important for myoblast differentiation (Kim et al, 2007). In addition, numerous studies have shown that actin-regulating proteins are involved in muscle differentiation and development (Bongiovanni et al, 2012;Nowak et al, 2009;Richardson et al, 2008). Suppression of Rho family small-GTPase activity by pharmacological inhibitors interferes with actin remodeling and the expression of myogenic factors such as myogenin and MRF4 (Bryan et al, 2005).…”
Section: Discussionmentioning
confidence: 99%
“…With respect to myogenesis, the WASP and ARP2/3 protein complexes are essential for myoblast fusion (Baas et al, 2012;Berger et al, 2008;Richardson et al, 2007), and WASP proteins promote myoblast migration (Kawamura et al, 2004). Although the mechanisms that direct myotube elongation are thought to mimic those of migratory cells (Bongiovanni et al, 2012), the role of Tropomyosin during myotube elongation has not been characterized.…”
Section: Introductionmentioning
confidence: 99%